O cuidado e a saúde mental de LGBTQIA+: as contribuições da terapia ocupacional - Depole, Bárbara de Fátima (Universidade Federal de São Carlos, 2023)
Discussions about gender and sexualities have gained more and more space in the Brazilian media, with the growing visibility of LGBTQIA+ people produced by the social movement and the increase in hate crimes and violence against this population. This entailed individual and collective psychic suffering, highlighting the importance of investigating mental health care for this population group. The conflicts and psychic suffering that this population faces are the result of the context of a heteronormative society. Thus, promotion, prevention and mental health care actions can reduce these effects and produce changes in hegemonic practices. In the Brazilian context, there are still few studies on mental health as a field for dialogue with LGBTQIA+ population policies. In addition, the dialogues achieved by the Occupational Therapy nucleus in relation to LGBTQIA+, aiming to promote mental health care from a perspective of social emancipation and production of subjectivity, are insufficient. To fill this gap, we carried out this research with the objective of identifying and analyzing potentials and limiting the field of Mental Health and the Occupational Therapy Center for Mental Health care for LGBTQIA+. Methodologically, we started from a study of the research-intervention type, using the cartography method, carried out in 2 stages. In step 1, quantitative and qualitative data were produced through online classes (QOL) distributed among mental health professionals and in step 2, qualitative data were deepened through group interviews with occupational therapists. The analyzes were carried out using the Gaze Interpolation technique. The results of the data obtained via QOL were presented in 3 subgroups: characterization of the participants, unique mental health processes of LGBTQIA+ and experienced violence. The results of the focus group with occupational therapists were presented in 5 categories: (1) Field and nucleus of mental health, (2) specificities of the nucleus of occupational therapy, (3) mental health care, (4) training practices and scenes everyday. It is concluded that mental health professionals claim to have insufficient knowledge about LGBTQIA+ social and health policies and gaps in their training in this regard. Even so, they identify specificities of this population in terms of mental health needs, as well as the care offered, in deep dialogue with the psychic suffering produced in the experience of family, structural/institutional violence and in the difficulties uniquely faced in the different cycles of life. Occupational Therapy has the potential to offer significant contributions, as long as there is an open dialogue and a perspective that aims at social emancipation and the production of subjectivity, considering the experiences and challenges faced by the LGBTQIA+ population in their daily lives, which are often related to the discrimination, stigma and social exclusion. An empathetic, critical, and inclusive approach can help create a safe and welcoming care environment for these people. Occupational Therapy can contribute by offering meaningful activities that help promote the mental health and well-being of the LGBTQIA+ population in their actions in the world. In addition, this Occupational Therapy care in the face of health and mental health demands can be directed towards the production of freer and emancipatory subjectivities, strengthening the powers of these subjects to individually and collectively resist the harmful effects of heteronormativity.
The care and mental health of LGBTQIA+: the contributions of occupational therapy
Keywords: Cuidado; Saúde mental; Terapia Ocupacional; LGBTQIA+; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL